Emergency department utilization among deaf and hard-of-hearing patients: A retrospective chart review. Issue 3 (July 2022) - James, Tyler G.; McKee, Michael M.; Miller, M. David; Sullivan, Meagan K.; Coady, Kyle A.; Varnes, Julia R.; Pearson, Thomas A.; Yurasek, Ali M.; Cheong, JeeWon
Abstract: Background: Deaf and hard-of-hearing (DHH) patients are an underserved priority population. Existing, although contextually limited, findings indicate that DHH patients are more likely to use the emergency department (ED) than non-DHH patients. However, little attention has been given to the differences in ED utilization by patients' language modalities. Objective: We hypothesized that DHH ASL-users and DHH English speakers would have higher rates of ED utilization in the past 36 months than non-DHH English speakers. Methods: We used a retrospective chart review design using data from a large academic medical center in the southeastern United States. In total, 277 DHH ASL-users, 1000 DHH English speakers, and 1000 non-DHH English speakers were included. We used logistic regression and zero-inflated modeling to assess relations between patient segment and ED utilization in the past 12- and 36-months. We describe primary ED visit diagnosis codes using AHRQ Clinical Classifications Software. Results: DHH ASL users and DHH English speakers had higher adjusted odds ratios of using the ED in the past 36-months than non-DHH English speakers (aORs = 1.790 and 1.644, respectively). Both DHH ASL users and DHH English speakers had a higher frequency of ED visits among patients who used the ED in the past 36-months (61.0% and 70.1%, respectively). The most common principal diagnosis code was for abdominal pain, with DHH English speakers making up over half of all abdominal pain encounters. Conclusions: DHH ASL users and DHH English speakers are at higher risk of using the ED compared to non-DHH English speakers. We call for additional attention on DHH patients in health services and ED utilization research.